Keabsahan Dan Kekuatan Hukum Alat Bukti Closed Circuit Television (CCTV) Dalam Pemberlakuan Tilang Elektronik - Darwoyo, Darwoyo; Abadi, Suwarno (Law and Humanity, 2024)
The application of an electronic ticket or Electronic Traffic Law Enforcement (ETLE) by the police is considered to have many problems and challenges for the police in the future, with reference to closed circuit television (CCTV) evidence that causes the gap in the use of CCTV (Closed Circuit Television) evidence in the criminal justice process, the first is the legal factor itself where the use of CCTV is not included in legal evidence in the Criminal Procedure Code, the two different perspectives which will result in different thoughts that will be accepted by someone, the three norms which becomes legalistic positivistic is not clear in certain cases. Legal basis for prosecution of traffic violations. According to Law Nomor 2 of 2009 concerning Traffic And Road Transportation, article 260 and article 262 who are authorized to take action against traffic violations using CCTV can carry out law enforcement such as investigations and investigations of criminal acts of LLAJ or other crimes, acts of handling of accidents, violations, and traffic jams by the Police and the pursuit, ambush, arrest, and prosecution of perpetrators and/or vehicles involved in crimes or traffic violations. The formulation of the legal problem contains points regarding the juridical review and application of the validity of ETLE as evidence in the trial. This research is a legal research with a normative juridical approach with a statutory and case approach, especially the decision of ticketing for traffic violations. The results of the research and discussion conclude that the use of CCTV (Closed Circuit Television) evidence can be used as evidence in the criminal justice process and the application of the e-Tilang system can reduce the number of traffic accidents.